Business, housing and credit cycles - Gerhard Rünstler; Marente Vlekke (European Central Bank (ECB), 2016)
We use multivariate unobserved components models to estimate trend and cyclical components in GDP, credit volumes and house prices for the U.S. and the five largest European economies. With the exception of Germany, we find large and long cycles in credit and house prices, which are highly correlated with a medium-term component in GDP cycles. Differences across countries in the length and size of cycles appear to be related to the properties of national housing markets. The precision of pseudo real-time estimates of credit and house price cycles is roughly comparable to that of GDP cycles.
Keywords: C32; E32; E44; 330; credit cycle; financial cycles; house prices; model-based filters; unobserved components models